Impact of the Electrification of Vehicles and Integration of Solar Photovoltaic Systems on Low-voltage Distribution Networks - Aschidamini, Gustavo L.; Holzbach, Matheus [UNESP]; Reinholz, Bradley A.; Metcalfe, Malcolm S.; Resener, Mariana (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The increasing integration of electric vehicles (EVs) and solar photovoltaic (PV) systems may impose challenges for the operation of power distribution networks such as network overloading and voltage issues. On the contrary, operating solutions with these low-carbon technologies may provide grid support and help mitigate grid congestion. This paper presents a study on the impact of the integration of EVs and solar PV generation on voltage issues, network loading and power losses in a low-voltage (LV) power distribution network. Quasistatic power-flow analysis is carried out for different levels of electrification of vehicles and solar PV systems penetration. A Monte Carlo simulation is used to capture uncertainty and variability both in load and generation. Case studies in a three-phase four-wire 18-bus LV distribution network demonstrate the grid impact for varying levels of EV integration with level 1 (L1) and level 2 (L2) charging, and solar PV system penetration levels. Switching from L1 to L2 charging lead to a 30 % increase in power losses during the summer and a 36 % increase during the winter, assuming 100 % EV penetration. Higher solar PV system penetration levels resulted in more significant reductions in active power losses during the summer season. Additionally, results also highlighted the significant impact of L2 charging on transformer loading and voltage.
Keywords: distributed energy resources; distribution systems; electric vehicles; electrification